FORMATION OF CREATIVE ACTIVITY OF OLDER PRESCHOOL CHILDREN IN THE PROCESS OF INTEGRATION OF SPEECH AND VISUAL ACTIVITY - Kotelianets, Yuliia (Mountain School of Ukrainian Carpaty, 2020)
The article reveals theoretical aspects of the formation of older preschool children’s creative activity, attention is paid to the integration of visual activity and development of speech. On the basis of research analysis the essence of the concept «creative activity» is clarified. Analyzing psychological and pedagogical research of creativity as a whole, summarizing the experience of scientists and teachers –practitioners on the formation of creative activity, we came to the conclusion that creative activity of older preschool children is an active state of personality, characterized by the desire to transform something, creation of personally significant material or spiritual product. It is emphasized that one of the indicators of the development of creative activity of the individual is the integrity of the children’s perception of works of art. It is established that organization of the process of forming creative activity is impossible without reliance on various activities of preschool children: development of coherent speech, word creation, decorative and constructive activity, etc. A number of components that will ensure the effectiveness of organizing the educational process in the kindergarden with the aim of forming the creative activity of older preschool children have been proposed. In our opinion, the formation of creative activity of older preschool children will be more effective if: Use predominantly integrated classes on the stage of reinforcement of the main material. The creative approach of the teacher will provide variation in the usage of teaching methods, tools and techniques. Use in addition to traditional some unusual materials for children's creativity. Using a variety of descriptive language (the language of literature, nature, art, music, etc.), creative problematic situations stimulate not so much external as internal creative activity (sensory and mental actions). In this way, a holistic approach is provided, the aim of which is a child himself, his worldperseption, feeling and understanding of the world.. It is not direct learning, but the awakening of the child's internal reserves to the transformation of knowledge, the stimulation of the hidden lines of individual development that can transform knowledge from a purpose into a means of development of the person – creator.